THE BEHAVIOR OF IRIDIUM BASED CATALYSTS IN THE SELECTIVE CATALYTIC REDUCTION OF NOX IN LEAN AUTOMOTIVE EXHAUST GAS CONDITIONS: A REVIEW (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The selective reduction of NO with hydrocarbons (HC-SCR), hydrogen (H2-SCR) and CO (CO-SCR) over iridium based catalysts in the O2-rich conditions is reviewed. The different factors that can affect catalytic activity are addressed for the three reactions (promoting and poisoning elements, operating conditions, etc.). For HC-SCR reaction, the important findings emerging from the studies revealed the effect of iridium particle size, role of support, effect of promoters, effect of reducing agent, and sulfur and water tolerance. The mechanism involved for HC-SCR reaction consists of NO oxidation to NO2 on basic sites of alumina and reaction with C3H6 to form acetate species which reduce NO into N2. In the case of H2-SCR, the activity of Ir is low and coexisting SO2 in the reaction gas considerably promotes NO reduction. The best support for Ir is SiO2. For CO-SCR, coexisting SO2 is also essential for CO-SCR on Ir/SiO2. The role of SO2 for both H2-SCR and CO-SCR on Ir/SiO2 is to keep Ir in the form of the catalytically active Ir metal state. WO3 and Nb2O5 considerably promote the activity of Ir/SiO2 for CO-SCR and catalyze CO-SCR even in the absence of SO2. Ir metal is the active species on WO3-promoted Ir/SiO2.